2021
DOI: 10.1101/2021.09.23.461245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain fatty acid binding protein exhibits non-preferential and mutation-resistant binding towards fatty acids

Abstract: Members of the fatty acid binding protein (FABP) family function as intracellular transporters of long chain fatty acids and other hydrophobic molecules to different cellular compartments. Brain fatty acid binding protein (FABP7) exhibits ligand-directed differences in cellular transport behavior. For example, when FABP7 binds to docosahexaenoic acid (DHA), the complex relocates to the nucleus and influences transcriptional activity, whereas FABP7 bound with monosaturated fatty acids remain in the cytosol. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…With the network-based ingredient screening model, we highlighted four major ingredients (GABA, stearic acid, tetradecanoic acid, and coumestrol) of ZSSG that might be able to regulate sleep quality. Taking stearic acid as an example, experimental research has demonstrated that this ingredient binds to FBAP7 [ 50 ]. FBAP7 knock-out mice displayed an increase in wake during the light phase, indicating that FBAP7 is required for normal sleep inhibition [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the network-based ingredient screening model, we highlighted four major ingredients (GABA, stearic acid, tetradecanoic acid, and coumestrol) of ZSSG that might be able to regulate sleep quality. Taking stearic acid as an example, experimental research has demonstrated that this ingredient binds to FBAP7 [ 50 ]. FBAP7 knock-out mice displayed an increase in wake during the light phase, indicating that FBAP7 is required for normal sleep inhibition [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the network-based ingredient screening model, we highlighted four major ingredients (GABA, stearic acid, tetradecanoic acid, and coumestrol) of ZSSG that might be able to regulate sleep quality. Taking stearic acid as an example, experimental research has demonstrated that this ingredient binds to FBAP7 [44]. FBAP7 knock-out mice displayed an increase in wake during the light phase, indicating that FBAP7 is required for normal sleep inhibition [45].…”
Section: Discussionmentioning
confidence: 99%